Systematic Literature Riview : Psikologi Pengasuhan dalam Keluarga Muslim terhadap Perkembangan Anak Usia Dini: Systematic Literature Review: Parenting Psychology in Muslim Families on Early Childhood Development - Arfah Andini; Rohinah; Suyadi (Universitas Ngudi Waluyo, 2026)
This study aims to analyze parenting psychology within Muslim families and its influence on early childhood development through a Systematic Literature Review (SLR). A total of 30 selected articles were reviewed to identify Islamic parenting patterns, the role of the family, and the contribution of the home environment to children’s moral, socio-emotional, cognitive, and psychological development. The findings reveal that Islamic parenting practices—implemented through role modeling, religious habituation, effective communication, and the application of Islamic values—significantly contribute to the formation of children’s character and moral foundations. Moreover, a harmonious and resilient family environment fosters emotional stability, enhances emotional regulation, and strengthens children’s social adaptability. Cognitive stimulation through educational play, early literacy activities, and family interactions also plays a crucial role in developing children’s language abilities, creativity, and cognitive functions. This study concludes that Islamic parenting provides a comprehensive approach that integrates spiritual, emotional, and cognitive dimensions to support early childhood development. It further recommends future research to explore the psychological mechanisms linking Islamic parenting practices to various developmental outcomes in children. ABSTRAK Penelitian ini bertujuan untuk menganalisis psikologi pengasuhan dalam keluarga Muslim dan pengaruhnya terhadap perkembangan anak usia dini melalui pendekatan Systematic Literature Review (SLR). Sebanyak 30 artikel terpilih dianalisis untuk mengidentifikasi pola pengasuhan Islami, peran keluarga, serta kontribusi lingkungan rumah terhadap perkembangan moral, sosial-emosional, kognitif, dan psikologis anak. Hasil kajian menunjukkan bahwa pengasuhan Islami yang diterapkan melalui keteladanan, pembiasaan ibadah, komunikasi efektif, dan penerapan nilai-nilai keislaman memiliki pengaruh signifikan terhadap pembentukan karakter dan moral anak. Selain itu, lingkungan keluarga yang harmonis dan memiliki ketahanan emosional terbukti menciptakan stabilitas psikologis, meningkatkan regulasi emosi, serta memperkuat kemampuan adaptasi sosial anak. Stimulasi kognitif melalui permainan edukatif, literasi awal, dan interaksi keluarga juga memberikan kontribusi besar pada perkembangan bahasa, kreativitas, dan fungsi kognitif anak. Penelitian ini menegaskan bahwa pengasuhan Islami merupakan pendekatan komprehensif yang menyatukan aspek spiritual, emosional, dan kognitif dalam mendukung perkembangan anak usia dini, serta merekomendasikan perlunya penelitian lanjutan mengenai mekanisme psikologis yang mengaitkan praktik pengasuhan Islami dengan berbagai aspek perkembangan anak.